Protests in Hong Kong (2019–2020): a Perspective Based on Quality of Life and Well-Being - Shek, Daniel T. L. (Applied Research in Quality of Life, 2020)
Triggered by the Fugitive Offenders and Mutual Legal Assistance in Criminal Matters Legislation (Amendment) Bill 2019 in Hong Kong (Extradition Bill), many protests have taken place in Hong Kong in 2019–2020. Using a perspective based on quality of life and well-being in different ecological systems, it is argued that the process of introducing the Bill is the “heat” which has ignited the “fuels” represented by 12 pre-existing and new issues in quality of life and well-being. These issues included distrust in the Central Government, lack of national identity, political dissatisfaction, economic strains, mental health threats, drop in family quality of life, lack of life skills education, lack of evidence-based national education in the formal curriculum, slow response of the Government, and alleged excessive use of force by the police. The fire has been intensified by “four strong winds”, including disinformation and misinformation, anonymity of the protesters, public support for the students, and support given by parties outside Hong Kong. Possible solutions in terms of promotion of quality of life and well-being with reference to the fire triangle are discussed.